PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Ramadhani, Kholifatur; Sari, Lita Permata; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2025)
The food and beverage industry plays a crucial role in the economy as it produces basic necessities for the Indonesian people. The development of this sector continues to increase in line with sustainable economic growth. In Indonesia, companies in this sector are experiencing significant growth, as evidenced by the increasing number of companies listed on the Indonesia Stock Exchange. The increase in the number of listed companies reflects the high public demand for this industry's products. The researcher chose Food and Beverage Companies as the research object because stocks in this sector tend to be more resilient to monetary or economic crises than other sectors. This is due to the fact that food and beverage products are basic necessities that remain in demand by the public, both in stable economic conditions and during crises. The purpose of this study is to analyze and test dividend policy in moderating the effect of Liquidity and Profitability on Stock Prices. The population in this study is Food and Beverage Companies with as many as 95 companies listed during the research period on the Indonesia Stock Exchange. The sampling technique was purposive sampling. The data analysis and hypothesis testing used Structural Equation Analysis – Partial Least Squares (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application indicate that liquidity has a positive but insignificant effect on stock prices, profitability has a positive but insignificant effect on stock prices, dividend policy has a negative but insignificant effect in moderating the effect of liquidity on stock prices, and dividend policy has a negative but insignificant effect in moderating the effect of profitability on stock prices.